2000
DOI: 10.1128/iai.68.12.6618-6623.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Malaria Vaccine Candidates Pvs25 and Pvs28 Completely Block the Ability ofPlasmodium vivaxTo Infect Mosquitoes

Abstract: Transmission-blocking vaccines are one strategy for controlling malaria, whereby sexual-stage parasites are inhibited from infecting mosquitoes by human antibodies. To evaluate whether the recently cloned Plasmodium vivax proteins Pvs25 and Pvs28 are candidates for a transmission-blocking vaccine, the molecules were expressed in yeast as secreted recombinant proteins. Mice vaccinated with these proteins adsorbed to aluminum hydroxide developed strong antibody responses against the immunogens, although for Pvs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 32 publications
4
129
0
1
Order By: Relevance
“…[1][2][3][4][5] A variety of determinants modulate transmission, including gametocyte quality, vector competence, and human innate and acquired immunity. Although host antibodies [6][7][8] have been shown to affect parasite infectivity for mosquitoes, transmission inefficiency is still observed in malaria hypoendemic regions where presence of antibody is thought to be low. 2,9 Previous work in Sri Lanka has suggested that humoral factors associated with the malarial paroxism reduces parasite infectivity for mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] A variety of determinants modulate transmission, including gametocyte quality, vector competence, and human innate and acquired immunity. Although host antibodies [6][7][8] have been shown to affect parasite infectivity for mosquitoes, transmission inefficiency is still observed in malaria hypoendemic regions where presence of antibody is thought to be low. 2,9 Previous work in Sri Lanka has suggested that humoral factors associated with the malarial paroxism reduces parasite infectivity for mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Interest in the potential of transmission-blocking vaccines to control or even eradicate malaria has recently increased; such vaccines work by inducing antibodies against components of the parasite's sexual stage forms, hence reducing infectivity of the reservoir, humans, for the obligate vector, Anopheles mosquitoes. [2][3][4][5][6][7][8][9][10][11] More detailed understanding of Plasmodium falciparum transmission stage biology, particularly ookinetes, would directly contribute to human transmission-blocking vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…vivax sexual stage surface proteins, orthologs of P. falciparum TBV candidates, also have been isolated and tested in transmission blocking experiments. Pvs25, a Pfs25 ortholog, is expressed on the surfaces of the insect-stages, zygotes and mature ookinetes, whereas Pvs28, a Pfs28 ortholog, is mainly expressed on retorts and mature ookinetes (Hisaeda et al 2000).…”
Section: P Vivax-derived Tbv Candidates -Pvs25 and Pvs28mentioning
confidence: 99%
“…P. falciparum proteins Pfs25, Pfs28, Pfs48/45, and Pfs230, and their orthologs in Plasmodium vivax, have been tested in transmission-blocking assays (Quakyi et al 1987;Kaslow et al 1988;Duffy & Kaslow 1997;Hisaeda et al 2000;Sattabongkot et al 2003;Malkin et al 2005;Outchkourov et al 2008). …”
Section: Parasite Antigen-based Tbvsmentioning
confidence: 99%